Daratumumab, Lenalidomide, and Dexamethasone (DRD), an Active Regimen in the Treatment of Immunosuppression-Associated Plasmablastic Lymphoma (PBL) in the Setting of Gorham’s Lymphangiomatosis: Review of the Literature - Lee, Matthew; Martin, Beth A.; Abdulhaq, Haifaa (Case Reports in Hematology, 2022)
Characterized by an aggressive course with a poor overall survival due to treatment refractoriness, plasmablastic lymphoma (PBL) is a rare variant of diffuse large cell B cell lymphoma. Gorham’s lymphangiomatosis or Gorham–Stout disease (GSD) is a rare skeletal condition of unknown etiology characterized by progressive bone loss and nonmalignant proliferation of vascular and lymphatic channels within the affected bone. Neither disease has a standard of care. We present a 23-year-old HIV-negative woman with GSD, managed medically with octreotide and sirolimus, who developed PBL. After progressing on V-EPOCH (bortezomib, etoposide, vincristine, cyclophosphamide, doxorubicin, and prednisone), she was treated with daratumumab, lenalidomide, and dexamethasone (DRD) therapy and achieved complete remission after two cycles with progression after eight cycles. This is a report of treatment of PBL with DRD therapy. Clinical investigations of the DRD regimen in PBL in conjunction with other agents to improve both depth and durability of response are warranted.